Vitamin D insufficiency in adults patients with low bone mass and osteoporosis in the Fundación Santa Fe de Bogotá 2008-2009 (2010)
Hypovitaminosis D is associated with osteoporosis, neuromuscular diseases, autoimmune diseases and cancer. The prevalence varies from 11–70% in different populations. Due osteoporosis is a common disease, we determined the prevalence of hypovitaminosis D associated with bone demineralization in FSFB population evaluated between August 2008 and July 2009, we reviewed age, gender, T-Score, Z-score. Values between 32–150 ng/ml were considered as normal. We found 460 25OHD results, 105 subjects with mineral density for DXA method, 80% female. Mean age for women was 66 years (SD ± 12.5, range 39–91) for women was 67.1 years (SD ± 12.2, range 39–91) for men was 61 years (SD ± 10.7, range 42–82). Mean 25OHD levels were 31 ng / ml (SD ± 17.6, range 8.2 to 110), for women 30.5 ng / mL (SD ± 16.1, range 10.6 to 96 ng / mL), for men 33.5 ng / mL (SD ± 23.4, range 8.2 to 110 ng / mL). 69,5% of cases were considered as vitamin D insufficiency, 45,7% mild, 23,8% moderate, and no cases of severe déficit. No significant difference between 25OHD concentrations and gender, or age were considered. Osteoporosis was correlated with 25OHD levels below 28 ng/ml (P=0,046) but not between low 25OHD and subjects with osteopenia. The vitamin D deficiency is highly prevalent in patients with osteoporosis and low bone mass and should be evaluated in the context of osteoporosis. © 2010 Asociación Colombiana de Reumatología